COMPRESSION OF FE3C TO 30 GPA AT ROOM TEMPERATURE - Li J.; Mao H.K.; Fei Y.; Gregoryanz E.; Eremets M.; Zha C.S. (My University, 2002)
Polycrystalline Fe3C (cementite) was compressed in a neon pressure medium to 30.5 GPa at 300 K using diamond-anvil cell techniques. Angular dispersive X-ray diffraction of Fe3C was measured using monochromatic synchrotron radiation and imaging plates. No phase transition was observed up to the highest pressure studied. The pressure-volume data were fitted to a third-order Birch-Murnaghan equation of state. With V0 constrained to a measured value of 155.28 A3, the best fit yielded a 300-K isothermal bulk modulus K0 = 174 ± 6 GPa, and its pressure derivative at constant temperature K0'=(K0/P)T= 4.8±0.8.
Keywords: FE3C; HIGH PRESSURE; PHASE STABILITY; BULK MODULUS; EOS